STRATEGI PENGEMBANGAN POLA KEMITRAAN ANTARA PTPN XII KEBUN KALISANEN DENGAN MITRA DAN MITRA DENGAN PETANI - Sitinjak, Kristina Br.; Soetriono, Soetriono; Kusmiati, Ati (JURNAL AGRIBISAINS, 2021)
The Kalisanen Plantation is one of the unit that is managed by PTPN XII who conducts the business in the fields of agribusiness as well as on the natural recources utilization optimizement. The resource that is optimized by Kalisanen Plantation is namely the use of the remaining company’s assets in the form of plantation land by means of partnership to a partner in the form of cooperation. The objectives of this study are: 1) to find out cooperation pattern between partners and PTPN XII Kalisanen Plantation and partners with the farmers, 2) to find out the income earned by farmers with PTPN XII Kalisanen Plantation in the pattern of partnership that is intertwined, 3) to find out the pattern of developmental strategy cooperated between partner and PTPN XII Kalisanen Plantation. The sampling collection method used quota sampling and expert judgment sampling. The data analysis method used descriptive analysis, revenue analysis, and the Analytic Hierarchy Process. The results showed that: 1) the partnership established by PTPN XII Kalisanen Plantation with partners is called the pattern of business cooperation, while the cooperation between the partners with farmers is called the operational partnership pattern. 2) partners with farmers of one hectare land in a period of one planting is profitable with an income of Rp 9.529.779. 3) priority criterion on partnership development strategy that exists between partner and PTPN XII Kebun Kalisanen is the criteria of land where as the priority alternative is to continue the Kerja Sama Usaha  activities of the land. Keywords: Cooperation Pattern, Revenue, Analytic Hierarchy Process